Genetic diversity of pneumococcal surface protein A (PspA) in paediatric isolates of non‐conjugate vaccine serotypes in Japan. Issue 8 (August 2018) - Kawaguchiya, Mitsuyo; Urushibara, Noriko; Aung, Meiji Soe; Morimoto, Shigeo; Ito, Masahiko; Kudo, Kenji; Kobayashi, Nobumichi
Abstract : Purpose. : Among the pneumococcal proteins, pneumococcal surface protein A (PspA) is considered the most promising candidate for a serotype‐independent vaccine. This study aimed to investigate the serotype, genetic diversity of PspA, lineage (genotype) and drug resistance traits of pneumococcal isolates from paediatric patients. Methodology. : A total of 678 non‐invasive pneumococcal isolates obtained from June to November 2016 were analysed. All isolates were characterized for PspA families, serotypes and macrolide resistance genes. Seventy‐one representative isolates of non‐vaccine serotypes (NVTs) were genetically analysed for the clade‐defining region (CDR) of PspA, as well as multi‐locus sequence typing (MLST). Results. : The detection rate of NVTs was 87.9 % ( n =596), including dominant NVTs 15A (14.5 %, n =98), 35B (11.8 %, n =80), 15C (9.3 %, n =63) and 23A (9.0 %, n =61). Most isolates (96.6 %) possessed macrolide resistance genes erm (B) and/or mef (A/E). PspA families 1, 2 and 3 were detected in 42.3, 56.6 and 0.6 % of isolates, respectively. Nucleotide sequences of CDR showed high identity (90–100 %) within the same PspA clade, although the CDR identity among different PspA families ranged from 53 to 69 %. All isolates of NVTs 23A, 10A, 34, 24, 22F/22A, 33F, 23B and 38 were from PspA family 1, while NVTs 35B, 15C, 15B and 11A/11D isolates were from family 2. In contrast, genetically distinct PspAs were found in NVTs 6C and 15A. PspA family 3/clade 6 was detected in only NVT serotype 37 isolates assigned to ST447 and ST7970, showing the mucoid phenotype. Conclusion. : The present study revealed the predominance of PspA families 1 and 2 in NVTs, and the presence of family 3 in serotype 37.